Effect of acute hypoxemia on cerebral blood flow velocity control during lower body negative pressure. Issue 4 (21st February 2018) - van Helmond, Noud; Johnson, Blair D.; Holbein, Walter W.; Petersen‐Jones, Humphrey G.; Harvey, Ronée E.; Ranadive, Sushant M.; Barnes, Jill N.; Curry, Timothy B.; Convertino, Victor A.; Joyner, Michael J.
Abstract: The ability to maintain adequate cerebral blood flow and oxygenation determines tolerance to central hypovolemia. We tested the hypothesis that acute hypoxemia during simulated blood loss in humans would cause impairments in cerebral blood flow control. Ten healthy subjects (32 ± 6 years, BMI 27 ± 2 kg·m −2 ) were exposed to stepwise lower body negative pressure (LBNP, 5 min at 0, −15, −30, and −45 mmHg) during both normoxia and hypoxia (Fi O2 = 0.12–0.15 O2 titrated to an SaO2 of 85%). Physiological responses during both protocols were expressed as absolute changes from baseline, one subject was excluded from analysis due to presyncope during the first stage of LBNP during hypoxia. LBNP induced greater reductions in mean arterial pressure during hypoxia versus normoxia (MAP, at −45 mmHg: −20 ± 3 vs. −5 ± 3 mmHg, P < 0.01). Despite differences in MAP, middle cerebral artery velocity responses (MCAv) were similar between protocols ( P = 0.41) due to increased cerebrovascular conductance index (CVCi) during hypoxia (main effect, P = 0.04). Low frequency MAP (at −45 mmHg: 17 ± 5 vs. 0 ± 5 mmHg 2, P = 0.01) and MCAv (at −45 mmHg: 4 ± 2 vs. −1 ± 1 cm·s −2, P = 0.04) spectral power density, as well as low frequency MAP‐mean MCAv transfer function gain (at −30 mmHg: 0.09 ± 0.06 vs. −0.07 ± 0.06 cm·s −1 ·mmHg −1, P = 0.04) increased more during hypoxia versus normoxia. Contrary to our hypothesis, these findings support the notion that cerebral blood flow control is not impaired during exposure to acute hypoxia and progressive central hypovolemia despite lower MAP as a result of compensated increases in cerebral conductance and flow variability. Abstract : The ability to maintain adequate cerebral blood flow and oxygenation determines tolerance to central hypovolemia. We tested the hypothesis that acute hypoxemia during simulated blood loss in humans would cause impairments in cerebral blood flow control. Contrary to our hypothesis, we found that cerebral blood flow control is not impaired during exposure to acute hypoxia and progressive central hypovolemia despite lower perfusion pressure as a result of compensated increases in cerebral conductance and flow variability.